Die Professoren der Universität Rostock im Dritten Reich. Ein biographisches Lexikon - Buddrus, Michael (Texte und Materialien zur Zeitgeschichte, 2007)
This encyclopaedia contains biographical portraits of the 189 professors who worked at the University of Rostock between 1932 and 1945. It represents the first complete list of professors at a German university during the Nazi era to include such comprehensive biographies. Among the types of information included is information on their careers, appraisals by superiors, Nazi offices and SED institutions, memberships and honours as well as their career after 1945. The authors have primarily relied on previously disregarded sources from various archives